Effectiveness and acceptance of virtual reality vs. traditional exercise in obese adults: a pilot randomized trial - Touloudi, Evlalia; Hassandra, Mary; Galanis, Evangelos; Pinnas, Gerasimos; Krommidas, Charalampos; Goudas, Marios; Theodorakis, Yannis (Frontiers in Sports and Active Living, 2025)
IntroductionObesity is a significant global health concern, increasing the risk of various diseases and health complications. Effective and engaging exercise interventions are urgently needed for obesity management. This pilot study examines the effectiveness of virtual reality (VR)-based exercise compared to traditional exercise, both combined with Self-Determination Theory (SDT)-based counseling, individuals with obesity.MethodsForty individuals with overweight/obesity were randomly assigned to either a VR-based exercise group (intervention) or a traditional exercise group (control), with both groups receiving SDT-based counseling over 4 weeks. Assessments were conducted pre- and post-intervention.ResultsParticipants in the VR-based exercise group showed significant reductions in BMI (2.6%) and body fat mass (5.3%) and consequently in hips circumference, compared to the control group. They also exhibited greater increases in physical activity levels, and improved psychological outcomes, including basic psychological needs (BPN), self-efficacy, self-esteem, and attitudes toward the program comparing with the control group. Moreover, the intervention group scored higher in interest/enjoyment and attitudes towards exercise compared with the control group and showed great results in perceived enjoyment, intention for future use, usability, and positive perceptions of using the VR system. Based on the participants’ interviews, VR-based exercise was found to be more enjoyable and engaging.DiscussionThese findings suggest that VR-based exercise combined with counseling is more effective than traditional exercise in reducing weight, increasing physical activity, and improving psychological outcomes individuals with obesity. The immersive nature of VR may enhance motivation and adherence to exercise programs, offering a promising alternative for obesity management. However, the study's small sample size, short duration, and reliance on self-reported measures may limit its generalizability. Future research should explore long-term adherence, effectiveness in diverse populations, psychological mechanisms behind engagement, and comparisons with emerging fitness technologies like AI-powered platforms.